Narrative Structures and Emotional Intelligence in Short Stories and Folktales: A Children's Literature Perspective - Liza Septa Wilyanti; Yundi Fitrah; Maizar Karim; Hary Soedarto Harjono (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the narrative structures and emotional intelligence content of short stories and folktales published in Bobo Magazine Edisi Koleksi Terbatas 50 Tahun: Cerpen Dongeng, with the aim of assessing their suitability as children’s literature. Employing a descriptive qualitative design, the research integrates structural and literary psychology approaches. Data were collected through purposive sampling of 13 texts, followed by close reading and note-taking techniques. Findings indicate that most stories follow a simple, linear narrative structure, with child or animal protagonists, familiar settings, and accessible language. Common themes include friendship, family affection, honesty, gender equality, and heroism—elements that align with the conventions of children’s literature. Structural analysis reveals that 8 out of 13 stories fully meet the criteria for children's literature. However, emotional intelligence analysis, based on Goleman's five dimensions (self-awareness, emotion regulation, self-motivation, empathy, and social skills), shows that only a few texts demonstrate all five components, while most focus primarily on emotional recognition and regulation. The study concludes that while these narratives structurally qualify as children’s literature, their representation of emotional intelligence remains limited. Given the educational value of emotional content in literature, the findings underscore the need for more intentional integration of emotional intelligence in children’s stories. The study is limited by its small corpus drawn from a single source and period (1993–2003). Future research should expand the corpus and explore alternative analytical approaches to deepen understanding of emotional intelligence in Indonesian children's literature.